2021
DOI: 10.3390/land10101074
|View full text |Cite
|
Sign up to set email alerts
|

Soil Quality Assessment Using Multivariate Approaches: A Case Study of the Dakhla Oasis Arid Lands

Abstract: A precise evaluation of soil quality (SQ) is important for sustainable land use planning. This study was conducted to assess soil quality using multivariate approaches. An assessment of SQ was carried out in an area of Dakhla Oasis using two methods of indicator selection, i.e., total data set (TDS) and minimum data set (MDS), and three soil quality indices (SQIs), i.e., additive quality index (AQI), weighted quality index (WQI), and Nemoro quality index (NQI). Fifty-five soil profiles were dug and samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 66 publications
(104 reference statements)
3
18
0
Order By: Relevance
“…Table 10 shows the support practices employing the land use/land cover and slope-classified images, which include different types of agricultural management practices based on altering flow patterns, gradients, or the direction of surface runoff with specific support and land practice effects. With minor restrictions on the soil quality grade, approximately 80% to 85% of the total study area was identified as suitable soil for agricultural use [64].…”
Section: Study Area Characteristicsmentioning
confidence: 99%
“…Table 10 shows the support practices employing the land use/land cover and slope-classified images, which include different types of agricultural management practices based on altering flow patterns, gradients, or the direction of surface runoff with specific support and land practice effects. With minor restrictions on the soil quality grade, approximately 80% to 85% of the total study area was identified as suitable soil for agricultural use [64].…”
Section: Study Area Characteristicsmentioning
confidence: 99%
“…In conclusion, if our management model is used in the planting process of contaminated soil, food and fodder safety risks can be effectively reduced and sustainable development of soil utilization can be realized in contaminated areas. This research suggests that satellite remote sensing and GIS application could be used by agricultural land use planners and land policy makers to select suitable lands for increasing crop production [50][51][52].…”
Section: Classified Management Pattern Of Contaminated Soilmentioning
confidence: 96%
“…Monitoring the dynamics of P 2 O 5 and K 2 O at the micro-level enables quality management of agricultural land and environmental protection, enabling the optimal application of mineral fertilizer [23,24]. At the macro-level, it enables monitoring and remediation of soil degradation [25].…”
Section: Soil Sampling Datamentioning
confidence: 99%